S-Cam A cryogenic camera for optical astronomy based on superconducting tunnel junctions. - Rando, N. (IEEE Transactions on applied superconductivity)
S-Cam is a cryogenic camera for ground-based astronomy using superconducting tunnel junctions (STJ's). It has been designed as a technology demonstrator, aiming to prove the potential of a new generation of single photon-counting detectors at a ground-based telescope. The camera is based on a 6×6 array of Ta-Al Josephson junctions, operating at about 350 mK and individually read out. For each detected photon, the absorption position, the arrival time, and the corresponding energy are measured. In this paper, we provide an overview of the cryogenic detector performance, a description of the S-Cam system, and a summary of the results obtained both during testing at ESTEC and during actual observations at the William Herschel Telescope (WHT) in La Palma, Spain. Initial astronomical observations were performed on the Crab pulsar, a neutron star spinning with a period of 33 msec at about 6000 light years from Earth